Hubungan Model Pembelajaran Berbasis Portofolio Dengan Keaktifan Belajar Pendidikan Agama Kristen (PAK) Siswa Kelas X SMK Negeri 1 Siborongborong Tahun pembelajaran 2023/2024 - Ester Malyana Silaban; Dame Taruli Simamora; Malani Simanungkalit (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to determine the positive and significant relationship between the Portfolio Based Learning Model and the Learning Activeness of Christian Religious Education of class X students at SMK Negeri 1 Siborongborong for the 2023/2024 academic year. The method used in this research is a descriptive quantitative research method. The population was all students of class The instrument for this research is a closed questionnaire. From the results of the positive relationship test calculations, the rcount value rcount=0.707> rtable=0.297(α=0.05, IK=95% N=50) thus it is known that there is a positive relationship between the portfolio-based learning model and active learning in education. Christian Religion and the results of the t test show the value and tcount=6.919> ttable (α=0.05, dk=n-2=48)=1.677, thus there is a significant relationship between the portfolio-based learning model and active learning in Christian Religious Education. So Ho is rejected and Ha is accepted. The research concluded that there was a positive and significant relationship between the portfolio learning model and the learning activity of Christian Religious Education for class